Undang-Undang No. 41 Tahun 2004 Tentang Wakaf Tunai - Ferdian, Fariz (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2020)
Waqf is worship in Islam which has two dimensions, namely the dimension of u’budiyah and the dimension ‘ijtima’iyah. Dimension of u’budiyah is a means of worship closer to Allah, while the dimension of ‘ijtima’iyah is a form of social responsibility and social concern for others. In the case of waqf, between Syafi'i and Hanafi mazhab there are differences in views. The Shafi'i school requires endowments to be with objects that last long and do not run out of goods even though the benefits have been taken, while the Hanafi school allows for the implementation of cash waqf for the reason of human relations and customs. In this study, it was wanted to know how the thought of Dayah Theologian in Northern Aceh specifically regarding the implementation of cash waqf. To examine this problem, field research methods were used by interviewing several Dayah Theologians who had an influence on the people of North Aceh. Most of the Acehnese Dayah Theologians argued that it was illegitimate cash waqf in Aceh, because it was not in accordance with the opinion of the Shafi’i school. The waqf requirement according to Syafi'i must be eternal despite its benefits. Whereas cash waqf is used only by spending the amount of money and it is considered alms, not waqf according to the Syafi'i's school.